The Influence Of Customer Relationship Management Dimensions On Customer Loyalty At Bank Bengkulu (A Case Study at Bank Bengkulu Bintuhan Branch) - Anggi Pratama Hakim; Ahmad Soleh; Silke Sachanovrissa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Bank Bengkulu has shown a positive performance increase in 2023. Third-party funds collected increased by 1.60% to Rp7.06 trillion, while credit granted rose by 1.03% to Rp6.30 trillion. The bank's total assets grew by 4.19% to Rp9.04 trillion, and total liabilities increased by 4.49% to Rp7.80 trillion. Total equity also experienced an increase of 2.39% to Rp1.24 trillion. This study aims to analyze the influence of Customer Relationship Management (CRM) dimensions on Customer Loyalty at Bank Bengkulu Bintuhan Branch. This research employs a quantitative causal method. Data collection used a closed questionnaire distributed to a sample of 230 Bank Bengkulu Bintuhan customers. The data collection process utilized an online survey disseminated through social media, specifically WhatsApp. Data analysis was conducted using multiple regression analysis with IBM SPSS 26 software. The analysis results show that the variables Complaint Resolution, Customer Knowledge, and Customer Empowerment have a significant positive influence on Customer Loyalty, leading to the acceptance of these three hypotheses. However, Customer Orientation does not have a significant influence on Customer Loyalty, resulting in the rejection of the fourth hypothesis. In conclusion, it is recommended that Bank Bengkulu strengthen complaint handling, product education, and Customer Empowerment to enhance loyalty. Service innovations, including digital banking and loyalty programs, can also help maintain customer engagement.